READING AND WRITING IN THE ESL/EFL CLASSROOM INTRODUCTION - Arechiga, Sara A. (HUMANITAS DIGITAL, 2022)
The purpose of this paper is to present the relation between reading and writing in the ESL/EFL classroom through an historical perspective. Also, the schema theory is examined through a general review of the reading-writing connection in order to provide a support to this viewpoint in L2 reading and writing. A brief description of the general features of the syllabus of the English course at the high school level of the Universidad Autónoma de Nuevo León is introduced. At this level, the general aim of the program is to develop reading comprehension in order to obtain and use information from English written texts in an EFL context. A general overview of research findings and theoretical views of reading in the ESL course and its connection to writing is presented since the interest of this study is provide some theoretical basis that explains and supports the near connection between reading and writing in ESL. This is presented with the intention of promoting the incorporation of writing in the English course at this level.